Amphibians and reptiles of the late Pliocene site of Ahl al Oughlam (Casablanca, Morocco) - (:unkn) unknown (My University, 2000)
The latest Pliocene site of Ahl al Oughlam (Morocco) has provided a rich and diverse herpetofauna: three amphibian taxa (Bufo sp., Bufo viridis and Hyla cf. meridionalis) and 16 reptile taxa (Testudo sp., Geochelone sp., cf. Crocodylus, Trogonophis darelbeidae n. sp., Blanus sp., Gekkonidae indet., Eumeces algeriensis, Chalcides sp., cf. Acanthodactylus, Ophisaurus koellikeri, Anguidae indet. [“morphotype” Anguis], Coluber hippocrepis, Malpolon sp., cf. Macroprotodon, Macrovipera sp. and Bitis sp.). Trogonophis darelbeidae n. sp. is mainly characterized by the peculiar insertion of the adductor muscle (= musculus adductor mandibulae) on the coronoid process, the premaxillary teeth which do not project anteriorly beyond the limit of the bone, and the rather weak tympanic crest of the quadratum. A great number of identified taxa is mentioned for the first time as fossils in Africa. At Ahl al Oughlam, the herpetofauna is constituted by tropical taxa, north African taxa and Ibero-maghrebian taxa. Compared with the Moroccan Miocene fauna, the Pliocene fauna seems to be characterized by an impoverishment in tropical taxa, and an enrichment in taxa of Iberomaghrebian type.
Keywords: African Research